Droplet‐digital polymerase chain reaction for detection of clinical hepatitis B virus DNA samples. Issue 12 (3rd September 2018) - Yang, Deping; Hu, Tingting; Wu, Xuan; Li, Ke; Zhong, Qi; Liu, Weiwei
Abstract : This study aimed to establish a quantitative droplet‐digital polymerase chain reaction (ddPCR) detection system for clinical hepatitis B virus (HBV) DNA in samples from patients with HBV infection with the aim of monitoring fluctuations and planning future antiviral treatments. Primers and probes for the conserved region of HBV DNA sequence (GenBank: AB554017.1) were designed by sequence alignment with the HBV DNA sequence in GenBank. The PUC57 plasmid containing the gene fragment was then synthesized according to the fragment amplified by the primer. Linear DNA templates were obtained by digestion of the PUC57 plasmid with Eco RI. Primer specificity was verified by electrophoresis and sequencing, and the plasmid was used to verify the performance of ddPCR. Serum levels of HBV DNA were then detected in 103 HBV patients by ddPCR and real‐time quantitative polymerase chain reaction (qPCR), and the consistency of the two methods was compared. The accuracy of the ddPCR assays showed good linear correlation ( R 2  = 0.9952). The ddPCR coefficient of variance (CV) for intrarun replicates reached 2.0%, and the CV value for inter‐run replicates reached 3.6%. The ddPCR could detect as little as one copy of the template, as demonstrated by continuous dilution. This assay system provided a novel and specific platform with a linear range of detection from 1 to 10 5  copies/µL. Serum samples were collected from 103 HBV patients, and HBV DNA levels quantiﬁed by ddPCR and qPCR showed good concordance based on the Bland‐Altman analysis. The 95% limits of agreement were log10 : 0.29 ± 0.55 copies/μL. Our ﬁndings demonstrated that ddPCR can improve the detection level of nucleic acid and quantify the nucleic acid concentration, which is suitable for the clinical detection of HBV DNA.